Migrating Countercurrent. The Example of European Cultural Residents in West Africa - (:unkn) unknown (My University, 2016)
This article analyses the migration of European artists and cultural professionals in West Africa. First, it shows that this cultural migration is connected to the structuring of a transnational artistic market at the crossroad of the development of European cultural cooperation in the African continent and the emergence of a market for “world cultures” in the North. Second, it shows the overlapping of professional, conjugal and family dynamics in the countercurrent migrant trajectories. Third, the article deals with the identity belongings developed by those that we call cultural residents, which grow aloof from the figure of the “expat” and the logic of the “project imported by White people”.
Keywords: African Research